Percutaneous heel cord release for clubfoot: A retrospective, multicentre cost analysis. (June 2018) - Hedrick, B.; Gettys, F. K.; Richards, S.; Muchow, R. D.; Jo, C.-H.; Abbott, M. D.
Purpose: The Ponseti method of treatment is the standard of care for idiopathic clubfoot. Following serial casting, percutaneous tendo-Achilles tenotomy (TAT) is performed to correct residual equinus. This procedure can be performed in either the outpatient clinic or the operating room. The purpose of this study was to evaluate the expense of this procedure by examining hospital charges in both settings. Methods: We retrospectively reviewed charts of 382 idiopathic clubfoot patients with a mean age of 2.4 months (0.6 to 26.6) treated with the Ponseti method at three institutions. Patients were divided into three groups depending on the setting for the TAT procedure: 140 patients in the outpatient clinic (CL), 219 in the operating room with discharge following the procedure (OR) and 23 in the operating room with admission to hospital for observation (OR+). Medical records were reviewed to analyze age, deformity, perioperative complications and specific time spent in each setting. Hospital charges for all three groups were standardized to one institution's charge structure. Results: Charges among the three groups undergoing TAT (CL, OR, OR+) were found to be significantly different (3840.60 versus 7962.30 versus 9110.00, respectively; p ≤ 0.001), and remained significant when separating unilateral and bilateral deformities (p < 0.001). There were nine total perioperative complications (six returns to the ER and three unexpected admissions to the hospital): five (2.3%) in the OR group, four (17.4%) in the OR+ group and none in the CL group. The OR+ group statistically had a higher rate of complications compared with the other two groups (p = 0.006). The total event time of the CL group was significantly shorter compared with the OR and OR+ groups (129.1, 171.7 and 1571.6 minutes respectively; p < 0.001). Conclusion: Hospital charges and total event time were significantly less when percutaneous TAT was performed in the outpatient clinic compared with the operating room. In addition, performing the procedure in clinic was associated with the lowest rate of complications. Level of Evidence: Therapeutic, Level III